2021
DOI: 10.24248/eahrj.v5i2.667
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Helicobacter Pylori in Specimens of Chronic Gastritis and Gastric Adenocarcinoma Patients: A Retrospective Study at University Teaching Hospital, Kigali, Rwanda

Abstract: Introduction: Helicobacter pylori (H. pylori) infection is the major cause of gastroduodenal diseases in populations of different ages.We conducted aretrospective studyusing archived tissue samples to determine the prevalence of H. pylori infection among patients diagnosed with gastritis and gastric adenocarcinoma by histopathology cases in one hospital in Rwanda. Materials and methods: Cases of chronic gastritis and gastric adenocarcinoma histologically diagnosed in a tertiary hospital in Rwanda over the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(51 reference statements)
0
0
0
1
Order By: Relevance
“…Regardless, the key factors that were reported to increase the risk for HPI in both HIC and LMIC were often correlated with the socioeconomic status of the households, overcrowding in housing, the number of people in the family, and older siblings [8,9]. In Rwanda, it was found that 80% of adult patients aged between 15 and 92 years with gastritis at CHUK from 2016 to 2018 [10]. Two approved methods for diagnosing HPI are usually categorized as non-invasive, minimally invasive, or invasive methods with upper gastro-intestinal endoscopy with a sample for biopsy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, the key factors that were reported to increase the risk for HPI in both HIC and LMIC were often correlated with the socioeconomic status of the households, overcrowding in housing, the number of people in the family, and older siblings [8,9]. In Rwanda, it was found that 80% of adult patients aged between 15 and 92 years with gastritis at CHUK from 2016 to 2018 [10]. Two approved methods for diagnosing HPI are usually categorized as non-invasive, minimally invasive, or invasive methods with upper gastro-intestinal endoscopy with a sample for biopsy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Los segundos están basados en la realización de endoscopia digestiva superior (EDS) con toma de biopsias e incluyen la prueba de la ureasa rápida (S = 80%-95% y E = 95%-100%), el cultivo microbiológico (S = 70% y E = 100%), las pruebas moleculares (S = 91% y E = 100%) e histopatología (S = 90%-95% y E = 95%-98%) (11) . Esta última tiene varias ventajas porque permite el diagnóstico de la infección, determina el grado de inflamación de la mucosa gástrica y permite evaluar la presencia de LPN (12) .…”
Section: Introductionunclassified